Analisis Penggunaan Powder Factor Terhadap Fragmentasi pada Lubang Ledak Vertikal dan Inclined di PT Aditya Buana Inter - Muhammad Rafliansyah1; Irvani Irvani; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
Based on the observations in PT Aditya Buana Inter it is known that the vertical blast hole blasting geometry is an average of burden of 2.5 m, spacing 2.413 m, height 6 m, stemming 2.3 m, primary charge 4 m and diameter of 3 inch or 0.076 m blast hole, the amount of explosives used is in average 667 kg each blasts and the result of the volume rocks in average 2090,25 m3 or 5225,63 tons and has average powder factor value is 0.318kg/m3 with the average of fragmentation is 72.05 cm. Forthe inclined blast hole blasting geometry is an average of burden of 2.5 m, spacing 2.413 m, height 6.21 m, stemming 2.3 m, primary charge 4.21 m and diameter of 3 inch or 0.076 m blast hole, the amount of explosives used is in average 231 kg each blasts and the result of the volume rocks in average 718.44 m3 or 1796,1 tons and has average powder factor value is 0.321 kg/m3 with the average of fragmentation is 26,82 cm. The right of proposal design the blasting geometry in the field by calculating the inclined blast holes with 15° slope, using the evaluation blasting geometry actualobtained has modification blasting geometry with the good calculating which is burden 2.5 m, spacing 2.5 m, stemming 2.56 m, height level9.21 m, subdrilling 0.6 m, and primary charge length7.25 m.The result for a Powder Factor was more efficient which is 0.260 kg/m3 compared with the blasting geometry actual the vertical blast hole is 0.318 kg/m3 and the blasting geometry actual the inclined blast hole is 0.321 kg/m3, and the distribution of rock fragmentation resulting from blasting which corresponds to the target where rocks measuring> 100 cm to 0% compared to the actual geometry of vertical explosive holes of 29.6%.